Effects of anaerobic regulatory mutations and catabolite repression on regulation of hydrogen metabolism and hydrogenase isoenzyme composition in Salmonella typhimurium. - Jamieson, D J (1986)
Hydrogen metabolism in Salmonella typhimurium is differentially regulated by mutations in the two anaerobic regulatory pathways, defined by the fnr (oxrA) and oxrC genes, and is controlled by catabolite repression. The synthesis of the individual hydrogenase isoenzymes is also specifically influenced by fnr and oxrC mutations and by catabolite repression in a manner entirely consistent with the proposed role for each isoenzyme in hydrogen metabolism. Synthesis of hydrogenase isoenzyme 2 was found to be fnr dependent and oxrC independent, consistent with a role in respiration-linked hydrogen uptake which was shown to be similarly regulated. Also in keeping with such a respiratory role was the finding that both hydrogen uptake and the expression of isoenzyme 2 are under catabolite repression. In contrast, formate hydrogenlyase-dependent hydrogen evolution, characteristic of fermentative growth, was reduced in oxrC strains but not in fnr strains. Hydrogenase 3 activity was similarly regulated, consistent with a role in hydrogen evolution. Unlike the expression of hydrogenases 2 and 3, hydrogenase 1 expression was both fnr and oxrC dependent. Hydrogen uptake during fermentative growth was also both fnr and oxrC dependent. This provided good evidence for a distinction between hydrogen uptake during fermentation- and respiration-dependent growth and for a hydrogen-recycling process. The pattern of anaerobic control of hydrogenase activities illustrated the functional diversity of the isoenzymes and, in addition, the physiological distinction between the two anaerobic regulatory pathways, anaerobic respiratory genes being fnr dependent and enzymes required during fermentative growth being oxrC dependent.